Enhanced crystallization, thermal properties, and hydrolysis resistance of poly(l-lactic acid) and its stereocomplex by incorporation of graphene nanoplatelets. (August 2017) - Girdthep, Sutinee; Sankong, Wenuka; Pongmalee, Asamaporn; Saelee, Tinnakorn; Punyodom, Winita; Meepowpan, Puttinan; Worajittiphon, Patnarin
Abstract: Poly(d -lactic acid) (PDLA) and graphene nanoplatelets were used as nucleating agents for poly(l -lactic acid) (PLLA). The graphene (1 wt%) shows a more pronounced effect than PDLA in facilitating PLLA crystallization. Graphene effect on crystallization of stereocomplex (SC) polylactide is also demonstrated. Although medium molecular weight PLLA was blended with a limited content (1 wt%) of low molecular weight PDLA in the presence of graphene (0.5 phr), SC melting temperature is slightly increased without the use of high molecular weight polylactide pair. Also, optimal graphene content (0.5 phr–1.5 phr) promotes crystallization of PLLA homocrystals in the three-component system (PLLA/PDLA/graphene). Graphene additionally enhances Young's modulus and barrier property to thermal degradation of both PLLA and SC systems. Furthermore, PLLA/graphene is more resistant to hydrolysis than PLLA. Likewise, PLLA/PDLA/graphene is more stable than PLLA/PDLA during hydrolysis. Graphical abstract: Highlights: Graphene nanoplatelets were more effective than PDLA in crystalizing PLLA. Thermal and mechanical properties of PLLA and stereocomplex were enhanced by graphene. Hydrolysis resistance of PLLA and stereocomplex was improved by graphene addition.